PELESTARIAN LINGKUNGAN HIDUP DI KABUPATEN SINJAI TELAAH HUKUM TATA NEGARA ISLAM - Junaid, Bismar; Jafar, Usman; HL, Rahmatiah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2023)
This study aims to examine and analyze environmental preservation in Sinjai Regency in the study of Islamic constitutional law. The research method used is field research (field research) which is qualitative descriptive with a juridical approach and a Syar’i normative approach. The results of this study indicate that the Regional Government of Sinjai Regency through the Environment and Forestry Service has carried out various work programs related to environmental preservation such as waste bank management, biopori (water absorption), tree planting in urban and coastal areas, institutional coordination in planning and making irrigation canal. In addition, the supporting factors in environmental preservation in Sinjai Regency are the availability of qualified human resources while the inhibiting factors for environmental preservation are the lack of budget, integrated planning, preparation of work programs, evaluation and monitoring of environmental development, and the availability of infrastructure such as reference laboratories to serve as reference for the regional sector and society in controlling pollution and environmental damage. In addition, preserving the environment from the siyasaH syar’iyyah perspective is both a responsibility and a mandate for humans as caliphs on earth.